Hafif ticari vasıtalarda pazar yapısı ve satın alma davranışlarının analizi - Çopur, Medar (Fen Bilimleri Enstitüsü, 1995)
Bu çalışmada hafif ticari vasıtalar sektörü ve bu sektördeki kullanıcılar incelenmiştir. Kullanıcıların satın alma davranışlarının endüstriyel ya da tüketici satın alma modellerinden hangisine daha çok benzediğini ortaya çıkarmak araştırmanın temel amaçlarındandır. Endüstriyel pazarlama teoride tüketim pazarlamasından radikal çizgilerle ayrılmasına rağmen son yıllardaki çalışmalarda bu iki dalın bu kadar kesin çizgilerle birbirinden ayrılmasının pazarlamada yaratıcılığa engel olduğu türünde görüşler yer almıştır. Araştırmanın sonuçları da bu yöndeki görüşleri destekler yöndedir. Endüstriyel talebe yakın olduğu varsayılan ticari araç talebi dayanıklı tüketim malları talebine benzer özellikler göstermektedir. Derinlemesine mülakat ve anket çalışmasından oluşan araştırma bulguları bu sonuçlan destekler yöndedir. Araştırma sonucunda hafif ticari vasıta kullanıcılarının özellikleri tanımlanmış, uygun pazarlama stratejileri konusunda önerilerde bulunulmuştur. Araştırma temelde hafif ticari vasıta müşterisinin bilinç eksikliğini ve bilinçlendirmesi gereğini ortaya koymuştur. Gelecekte bu gerçeği görüp stratejilerini oluşturan firmalar başarılı olacaktır.

This research analyzes the light commercial vehicles segment. It aims to identify industrial - consumer marketing differences clearly. Light commercial vehicle owners are considered to be industrial customers since they use these products either to transport goods professionally and make a living or again transport goods to help to realize the real function of their business. Both types of these demands seem industrial. Theoretically speaking sounds nice but is it supported empirically? First industrial marketing is clearly identified. Then organizational and consumer behaviors are discussed. How they differ is the next subject. Then comes the research which aims to support the theoretical founding. The last chapter is the conclusion and researcher's proposals. Starting from the next paragraph first some basic term definitions will be made then the consumer industrial marketing differences will be discussed and organizational buying behavior will be defined, a brief about the conclusion of the research and researcher's proposals will follow. Consumer goods are goods destined for use by the individual ultimate consumer and in such form that they can be used by him without further commercial processing. On the other hand, industrial goods are characterized as goods which are used in producing consumers' goods, other business or industrial goods and services and/or in facilitating the operation of an enterprise, may (sic) include land and buildings for business purposes, equipment (installation and accessory), operating supplies, raw materials and fabricated materials. There must be an awareness that in many instances a specific commodity may either be an industrial good or a consumer good, depending upon the use to which it is put. Consumer goods marketing includes those business activities involved in the flow of goods and services destined for use by the individual ultimate consumer in such form that they can be used by him/her without further processing. And industrial goods marketing includes business activities involved in the flow of goods and services used in producing consumer goods, other business or industrial goods, and / or in facilitating the operation of an enterprise.
Analysis of light commercial vehicles market structure and buying behavior
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1995
Keywords: İşletme; Otomotiv endüstrisi; Pazarlama; Piyasa payı; Satınalma davranışı; Business administration; Automotive industry; Marketing; Market share; Purchasing behavior